2006
DOI: 10.1007/s10531-004-1062-8
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Refugium Value of a Large Mesa for Grasshoppers in South Africa

Abstract: A 3-year study was undertaken on and around a prominent South African mesa to determine its role for grasshoppers in a sea of grazed flatlands. The number of grasshopper species and individuals on the summit, slopes and flatlands varied significantly in relation to measured environmental variables. The summit, through inaccessibility to livestock grazing, was effectively a conservation refugium for one highly responsive grasshopper species, Orthochtha dasycnemis. There was no significant difference in species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Samways () showed how certain montane grasshoppers occupied hilltops as thermal refugia, which demonstrated how grasshopper distribution can be significantly influenced by topography. In fact, elevation is seen as a proxy for microclimatic heterogeneity, and is a well‐known determinant of grasshopper community patterns in space (Kemp et al ., ; Samways, ; Wettstein & Schmid, ; Gebeyehu & Samways, ). Thus, grasshopper assemblages can respond to multiple environmental conditions within a landscape (Samways & Sergeev, ).…”
Section: Discussionmentioning
confidence: 99%
“…Samways () showed how certain montane grasshoppers occupied hilltops as thermal refugia, which demonstrated how grasshopper distribution can be significantly influenced by topography. In fact, elevation is seen as a proxy for microclimatic heterogeneity, and is a well‐known determinant of grasshopper community patterns in space (Kemp et al ., ; Samways, ; Wettstein & Schmid, ; Gebeyehu & Samways, ). Thus, grasshopper assemblages can respond to multiple environmental conditions within a landscape (Samways & Sergeev, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that large‐scale alteration in vegetation patterns by wild ungulates does not directly influence the Orthoptera communities in the SNP as abundance and species diversity did not differ between the two vegetation types. We know of only three previous studies considering Orthoptera abundance in relation to wild ungulates at the landscape scale: (i) Samways and Kreuzinger (2001) found higher grasshopper densities in lightly grazed habitats compared to heavily grazed habitats, explaining the difference by increased habitat heterogeneity; (ii) Gebeyehu and Samways (2006) found that species richness and abundance decreased with altitude and grazing pressure, with concomitant changes in community composition driven by a variety of environmental factors (e.g. grass height, grass greenness, and percentage of bare soil); and (iii) Joern (2004) reported higher Orthoptera numbers under wild bison grazed – compared to ungrazed – conditions in the Konza tall‐grass prairie in Kansas (USA), explaining his findings by increased forage quality and habitat heterogeneity in grazed vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…A large mesa in South Africa acted as a refuge for Orthoptera in comparison to the heavily grazed flatlands which surrounded it (Gebeyehu and Samways 2006). The summit, which was inaccessible to grazing livestock, was an important conservation refuge for one grasshopper species, Orthochtha dasycnemis.…”
Section: The Effect Of Grazingmentioning
confidence: 99%